The Downstream Well-Being Effect of Encounters with the U.S. Criminal Justice System - Sanders, Christopher A.; King, Laura A. (Social justice research, 2025)
This study examines the relationship between encounters with the criminal justice system and psychological well-being in a large U.S. sample. This project builds upon previous research about the negative outcomes tied to such encounters by examining potential long term negative effects on people’s subjective well-being and sense of meaning and purpose in life. Panel study participants indicated their lifetime exposure to the criminal justice system, and then, about two years later, indicated their current subjective well-being and sense of meaning and purpose in life. Our findings reveal that the number of past police arrests is associated with reductions in well-being, with the first arrest showing the strongest effect. When controlling for number of previous arrests, no other aspect of exposure to the criminal justice system (e.g., the presence of a criminal conviction, amount of time spent detained) was significantly related to well-being. Race and gender predict encounters with the criminal justice system, but the relation to well-being remains consistent across demographics. Given the importance of meaning and life purpose as a protective factor against trauma and stress, it is vital to understand how first encounters with the criminal justice system, in particular, are related to people’s sense of purpose and meaning.